PENGUJIAN LABORATORIUM DAN PERAMALAN PRODUKSI MINYAK MENGGUNAKAN METODE KOMBINASI VIBROSEISMIK DENGAN INJEKSI SURFAKTAN - Ariya Wibowo, Agung
A combination method of vibroseismic and surfactant injection namely vibrosurfactant aims to obtain maximum oil productions and identify its potential as a new innovation in enhanced oil recovery method. This research observes the effect of vibrosurfactant methods to maximize oil production through improving several parameters that can affect to rock and fluid properties in the reservoir. The analysis of these combination methods was carried out with laboratory experiment, fluid flow modeling, and forecasting of the oil production performance of wells. Laboratory testing was carried out by coreflooding experiment using vibroseismic methods and surfactant injection sequentially. The experiment was divided into 3 (three) major scenarios, that is vibroseismic scenario, surfactant injection scenario, and the combination of two methods called vibrosurfactant scenario. The parameters that influence the combination methods of vibroseismic and surfactant injection are vibration frequency and surfactant concentration, which the frequency can affect on dislodging process and merging oil droplets that detached from rock pore wall (coalescence) and the surfactant concentration gives an effect on decereasing interfacial tension and oil viscosity so that it can produce oil more optimum. At this stage the vibrosurfactant scenario was obtained using 20 Hz of vibration frequency and 2% of surfactant concentration as the most optimum scenario with a recovery factor of 69.26%. Laboratory experiment results are then used to develop mathematical models of fluid flow using Del Rio fluid flow equation. Sensitivity variation using mathematical model results an optimum vibration frequency of 20 HZ and the results of oil viscosity as a parameter that represent surfactant concentration with the most optimum value of viscosity reduction is 0.75 cp. Forecasting of well production performance is done by upscaling mathematical models from the laboratory scale into the field scale. Decline curve analysis was carried out on 7 (seven) well production data at Field X as abaseline for the simulation results using the vibroseismic and vibrosurfactant methods. The simulation resulted in a cumulative increase in total oil production for seven wells of 207,680 STB with wibroseismic methods and 230,623 STB with vibrosurfactant methods which the average percentage of the difference between the two methods is 9,39%. Based on the overall results of the study, surfactant injection in the vibrosurfactant method can be used to increase the effectiveness of vibroseismic in order to produce more optimal oil production.